1978
DOI: 10.1172/jci108955
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Role of Thyrotropin-Releasing Hormone in the Regulation of Thyroid-Stimulating Hormone and Prolactin Secretion in the Rat

Abstract: A B S T R A C T The physiological role of thyrotropinreleasing hormone (TRH) in the regulation of thyrotropin (thyroid-stimulating hormone, TSH) and prolactin (Prl) secretion has been assumed but not proven. Stimulation of their release requires pharmacologic doses of TRH. Lesions of the hypothalamus usually induce an inhibition of TSH secretion and an increase in Prl. To determine whether TRH is essential for TSH and Prl secretion in the rat, 0.1 ml of TRH antiserum (TRH-Ab) or normal rabbit serum was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(35 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…Control rats were injected with 0.3 ml normal rabbit serum (NRS). The TRH-AS employed in these experiments displayed a binding capacity of 48 nM/liter and when used in the TRH radioimmunoassay in a dilution of 1:50,000, 30% of [1251]TRH was bound to antiserum (6). Blood was obtained by heart puncture from the pregnant rats under light ketamine anaesthesia, the fetuses were removed through cesarian section, and fetal blood was collected from the trunk, after decapitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control rats were injected with 0.3 ml normal rabbit serum (NRS). The TRH-AS employed in these experiments displayed a binding capacity of 48 nM/liter and when used in the TRH radioimmunoassay in a dilution of 1:50,000, 30% of [1251]TRH was bound to antiserum (6). Blood was obtained by heart puncture from the pregnant rats under light ketamine anaesthesia, the fetuses were removed through cesarian section, and fetal blood was collected from the trunk, after decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the TRH control of TSH seiLretion has been derived mainly from animal studies with hypothalamic lesions, basal hypothalamic deaffereintation, or heterotopic pituitary transplantation, all of which result in a decrease in pituitary TSH secretion (1)(2)(3)(4)(5). Recently, we and others (6)(7)(8) have reported that passive immunization with TRH' antibody results in a marked decrease in the basal and cold-stimulated TSH secretion in the normal and hypothyroid adult riat, although the role of endogenous TRH in maintaining increased serum TSH in the hypothyroid rat has been questioned (9).…”
Section: Introductionmentioning
confidence: 99%
“…the hypothalamic-pituitary-thyroid (HPT) axis. Hypophysiotropic neurons within the paraventricular nucleus of the hypothalamus produce thyrotropinreleasing hormone (TRH), which in turn stimulates the thyrotroph cells of the anterior pituitary to synthesize and secrete thyroid-stimulating hormone (TSH) (Harris et al 1978). TSH then stimulates the thyroid gland to produce thyroid hormones in the form of thyroxine (T 4 ) and triiodothyronine (T 3 ) (Miot et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thyrotropin-releasing hormone (TRH) is produced in the paraventricular nucleus of the hypothalamus 111 and stimulates the secretion of thyroid-secreting hormone (TSH) from the anterior pituitary 112,113 . TSH in turn regulates the biosynthesis and release of thyroid hormone 114 .…”
Section: Thyrotropin-releasing Hormonementioning
confidence: 99%